Effect of Carrying Two Types of Packs in Two Heights of Placement (Lumbar and Thoracic) on some Kinematics Variables of Primary Schoolboys - Ali Akbar Jadidian; Mohammad Hossein Alizadeh; Elham Shirzad (Vesnu Publications, 2020)
Introduction: The present study is conducted with the aim to investigating the effect of carrying backpacks and modified packs (with three bags that distribute the load equally in front and back of trunk) in two heights of placement including lumbar and thoracic, on craniovertebral angle, trunk angle, and the angle of hip and knee joints among the 8-11-year-old schoolboys during walking.Materials and Methods: Considering the inclusion and exclusion criteria, 27 schoolboys participated in the study and fulfilled five tasks including walking without a pack, carrying backpack on lumbar area, backpack on thoracic area, modified packs on lumbar area, and modified packs on thoracic area. Then, the photogrammetry of the right side was performed by a camera (Panasonic, Japan). The target angles were measured as single-blind with Kinovea motion analysis software. Repeated measure analysis of variance (ANOVA) was used to compare tasks.Results: The results showed significant decrease in craniovertebral angle (increased forward head posture) in the task of carrying backpacks on thoracic area in contrast with the lumbar area, as well as increase in trunk forward lean while carrying packs (P < 0.05) that was significantly higher in the backpack carrying tasks (P < 0.05). But in craniovertebral angle, significant difference was not seen while carrying modified packs in contrast with the control group (P > 0.05).Conclusion: Carrying packs on lumbar area caused less postural variations, thus seeming better. Changing the position of the load concentrated on the back can more affect the kinematic parameters of schoolboys. The modified pack carriage only caused a little trunk forward lean which was lesser than that of backpack carriage, so it can be a good alternative for students' backpack.